2014
DOI: 10.3150/13-bej555
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive sensing performance lower bounds for sparse signal detection and support estimation

Abstract: Please check the document version of this publication:• A submitted manuscript is the version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 31 publications
5
50
0
Order By: Relevance
“…Future work will consider the extension of the techniques in this paper to estimation loss functions other than MSE, to analogous policies for adaptive spectrum sensing [10], to other tasks such as signal support recovery, and to direct analysis of policies with more than two stages. In addition, it would be desirable to determine fundamental limits on adaptive sensing, along the lines of [12], [13], for the problem considered in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Future work will consider the extension of the techniques in this paper to estimation loss functions other than MSE, to analogous policies for adaptive spectrum sensing [10], to other tasks such as signal support recovery, and to direct analysis of policies with more than two stages. In addition, it would be desirable to determine fundamental limits on adaptive sensing, along the lines of [12], [13], for the problem considered in this work.…”
Section: Discussionmentioning
confidence: 99%
“…The behavior of the minimax risk has been analyzed for various class choices C [1], [7], [11], [22]. Detection and estimation in this model has been analyzed under adaptive sensing in [13] and [19], where it is shown that, perhaps surprisingly, all sufficiently symmetric classes C lead to the same almost matching necessary and sufficient conditions for detection. This is quite different from the non-adaptive version of the problem where size and structure of C influence, in a significant way, possibilities of detection (see [1]).…”
Section: Related Workmentioning
confidence: 99%
“…Here, in order to bound the maximum KL divergence, we will take an approach similar to [13] for detection-of-means under adaptive sensing, although our setup differs slightly. In [13], the testing procedures measure a single coordinate at a time, while we need multiple measures per step in order to capture correlations. We have the following necessary condition.…”
Section: Lower Boundsmentioning
confidence: 99%
See 2 more Smart Citations